Factors that affect employee engagement in Airod Sdn Bhd / Nurul Hanisah Mohd Isa - Mohd Isa, Nurul Hanisah (Faculty of Business and Management, 2017)
The purpose of the research was to identify factors that affect employee engagement in Airod Sdn Bhd. The factors consist of three independent variables which are leadership, rewards and recognition, and communication whereas employee engagement becomes the dependent variable in this study. The research was carried out with the sample size of minimum 132 employees from the total population of 200 employees in Airod Sdn Bhd. Moreover, the data has been collected by using a survey questionnaire that need to be answered by respondents. In addition, the researcher used Convenience Sampling method in order to gain the data from respondents. Based on the result, the findings show a significant correlation between the dependent variable and independent variables.